Analisis Risiko Ergonomi Lingkungan Kerja Fisik pada Karyawan Kantor Menggunakan Metode Rapid Office Strain Assessment (ROSA) - Savira Febryanti Suherman; Tangguh Dwi Pramono (Applied Business and Administration Journal, 2023)
The use of computers is now inseparable from office work completion activities. The place where routine business or commerce takes place is the office. Workers are required to spend nearly all of their time operating the computer while seated in front of the monitor due to the computerized system for office work. Long-term computer use combined with improper posture can result in eye fatigue as well as muscle and back injuries and fatigue. Work stances like sitting, composing, and gazing at a PC screen will influence the state of being of representatives. Employee performance will suffer as a result of poor ergonomic work postures, which will put employees at risk and make them more likely to become exhausted. Based on the rapid office strain assessment method, this study was conducted to determine the ergonomic risk analysis of the physical work environment in the work posture of office employees. The Rapid Office Strain Assessment (ROSA) analysis method was used in this observational descriptive study. A method for measuring ergonomic risk in the workplace at an office is the ROSA method. Perceptions were made to straightforwardly see the communication between work stances and office offices as office support components in 15 representatives who turned into the examination test. The findings revealed that 10 employees had a level of ergonomic risk that was low, while the remaining 5 employees had a level of ergonomic risk that was moderate. The reason for high ergonomic gamble lies in ergonomic offices that are not as per ergonomic standards and absence of representative mindfulness in making a solid work culture. Modernizing office facilities, spreading awareness of office ergonomics, and requiring employees to stretch are all necessary improvements. Keywords: Office Ergonomics, Ergonomic Risk, Rapid Office Strain Assessmentt, Work Posture